Dickens's comic art: a study of the comic element in Dombey and .son, little Dorrit, and great expectations - Ian, Nicholas McBride (Department of Drama, 2023)
The new Clarendon Dickens Edition (General Editors: John Butt and Kathleen Tillotson), was not available at the time' of writing for all of the novels which are studied in this thesis. Considerations of consistency and availability, therefore, dictated my use of the New Oxford Illustrated Edition of Dickens's novels. Details of the three main works referred to in this thesis are as follows: Dealings with the Firm of Dombey and Son (1848; rpt. Oxford: O.U.P., 1950) Little Dorrit (1857; rpt. Oxford: O.U.P., 1953) Great Expectations (1861; rpt. Oxford: O.U.P., 1953) All other quotations and references to Dickens's. works also refer to the New Oxford Illustrated Edition, unless otherwise noted. I have consulted the Clarendon Dickens (Variorum) Edition where applicable, and the few pertinent textual variations have been duly footnoted. All word-divisions at line endings are sanctioned by the Collins Ge~ Dictionary of Spelling and Word Division, compiled by S.8. Marshall (London: Collins, 1968).